1991
DOI: 10.1111/j.1476-5381.1991.tb12415.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of action of platelet activating factor in the pulmonary circulation: an investigation using a novel isotopic system in rabbit isolated lung

Abstract: 1 Rabbit isolated lungs were perfused via the pulmonary artery with Tyrode solution containing 4.5% Ficoll and 0.1% bovine serum albumin at a constant rate of 20 ml min-'. Lung perfusate was drawn for alternating 5min periods from two reservoirs, one containing '25I-albumin and the other unlabelled albumin to wash out the intravascular label. Microvascular '25I-albumin leakage was determined from the count remaining at the end of the washout phase with an external gamma scintillation probe. In addition, perfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Sakai et al (1989) observed that PAF perfusion increased pulmonary arterial and microvascular pressure as well as oedema and protein extravasation in rat isolated lung. These findings have been confirmed recently by Seale et al (1991). Intravenous injection of PAF induced systemic hypotension in vivo (Caillard et al, 1982), pulmonary hypertension (Heffner et al, 1983), and increased protein extravasation in airways perfused by the systemic circulation, whereas oedema and protein permeability were not affected by PAF in lung parenchyma perfused by the pulmonary circulation (O'Donnell & Barnett, 1987;Sirois et al, 1988;1990;Chen et al, 1990).…”
Section: Introductionsupporting
confidence: 70%
“…Sakai et al (1989) observed that PAF perfusion increased pulmonary arterial and microvascular pressure as well as oedema and protein extravasation in rat isolated lung. These findings have been confirmed recently by Seale et al (1991). Intravenous injection of PAF induced systemic hypotension in vivo (Caillard et al, 1982), pulmonary hypertension (Heffner et al, 1983), and increased protein extravasation in airways perfused by the systemic circulation, whereas oedema and protein permeability were not affected by PAF in lung parenchyma perfused by the pulmonary circulation (O'Donnell & Barnett, 1987;Sirois et al, 1988;1990;Chen et al, 1990).…”
Section: Introductionsupporting
confidence: 70%
“…['251I]-fibrinogen extravasation induced by NKA or [P-Ala8]NKA(4-10) was examined after pretreatment with the selective NK2 antagonist, SR 48968. The results (Figure 3 c In this study we used [I251]-fibrinogen, a recently described 10 10 marker of protein extravasation (Pedersen et al, 1991) in place of albumin which is more commonly used (Seale et al, 1991;Lotvall et al, 1991). Fibrinogen is a large protein molecule found in the blood (400 kDa compared to albumin 55 O 69 kDa) (Harper, 1975 (Saldeen, 1969).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of P AF's vascular action is attributed to formation of gaps between epithelial cells (BJORK and SMEDEGARD 1983;HUMPHREY et al 1984;BOLIN et al 1987) leading to protein leakage (TABOR et al 1992) in adjunction with vasoconstriction (SAKAI et al 1989;SEALE et al 1991) and the influence of leukocytes and platelets (SIROIS et al 1994) as well as that of superoxide dismutase (HUANG et al 1994). In contrast, PAF also has priming effects on pulmonary arterial reactivity to other autacoids (OHAR et al 1993) or other substances, e.g., protamine .…”
Section: Pulmonary Edemamentioning
confidence: 99%